The Role of Motivation Factors in Organizational Behavior: Theoretical-Methodological Analysis - Kykhtuik, Oksana (Psychological Prospects Journal, 2019)
The article deals with theoretical and methodological analysis of the basic theories of motivation and the role of motivational factors in organizational behavior is determined. The present trends, changes taking place in the world in the study and orientation of organizational behavior are substantiated. The role of the main motivational factors influencing the organizational behavior of the individual is described. The following main processes of organizational behavior were identified: governance, power and politics, information and communication, decision-making, conflicts and negotiations, mediation, change, stress. The theoretical analysis of the main theories of motivation: reinforcement, substantive, procedural. It has been discovered that each of these scientific concepts focuses on one or more motivational factors: reinforcements or rewards; needs or knowledge, satisfaction, efficiency. The issue of the need for an integrated approach to motivating employees in organizations has been updated. The concept of the organizational environment and its influence on the development of the personality in the organizational structure are highlighted. An important motivational factor of the personality in the workplace as a satisfaction with the united work integrates all the existing theories of motivation. The influence of remuneration as a motivational factor on satisfaction with work of a worker is described. Taking into account all motivational factors will contribute to the successful development, the competitiveness of organizational structures, the possibility of becoming an international market. Perspective is the need to develop and implement training on the personal development of employees, teaching aspects of psychology of motivation in the form of socio-psychological training for organizational structures.